(untitled) (Medicine Today, 2018)
Eclampsia constitutes a leading cause of maternal and perinatal mortality and morbidity worldwide. To assess health seeking behaviour of the family members and the patient with eclampsia. This cross sectional study was carried out on 100 eclampsia patients in the Institute of Child and Mother Health (ICMH), Dhaka from December’ 2004 to November’ 2005. In this study it was found that more vulnerable age group was 19-27 (49.0%) and primaegravida was 52.0%. This study revealed that knowledge about preconceptional health checkup was 3.0%, antenatal checkup was 52.0%, causes of preeclampsia & eclampsia in pregnancy was 20.0%, plan of delivery was 16.0%, safe hospital delivery was 20.0%, savings of money for delivery was 32.0%, transportation to hospital was 26.0%, consequences of severe preeclampsia & eclampsia was 9.0% of the study population. This study also showed that 82.0% and 77.0% of the patients had negative attitude towards antenatal check up and hospital delivery respectively. Only 58.0% of the patients had antenatal checkup. In this study 58.0% and 42.0% of the patients were referred to hospital by trained birth attendant (TBA) and relatives respectively. Half of the patients were referred by relatives. The present study showed that the maternal death was 4.0% and perinatal death was 27.0%. Lack of proper knowledge about consequences of eclampsia and severe preeclampsia and poor knowledge about proper antenatal care and negative attitude towards hospital delivery affects the outcome of both maternal and fetal condition. Medicine Today 2018 Vol.30(2): 67-70